Autothermal reforming of heavy-hydrocarbon fuels by morphology controlled perovskite catalysts using carbon templates. (1st January 2017) - Jeon, Yukwon; Lee, Chanmin; Rhee, Junki; Lee, Gicheon; Myung, Jae-ha; Park, Myunggeun; Park, Joo-Il; Einaga, Hisahiro; Shul, Yong-Gun
Graphical abstract: The synthesis of morphology-controlled perovskite catalysts using activated carbon templates was introduced for the applications to the heavy-hydrocarbon autothermal reforming. The effect of the carbon templates was investigated to determine how carbon templates influence to the formation of the perovskites. Hollow fiber and porous grain perovskites provided higher specific surface areas than the non-templated perovskite, which showed better activity and durability on the H2 production from heavy-hydrocarbon. Abstract: A novel synthesis of morphology-controlled perovskite networked with LaCr0.8 Ru0.2 O3 nanoparticles was introduced using activated carbons as sacrificial templates. These catalysts were used for the hydrogen production by heavy-hydrocarbon autothermal reforming. To investigate the effect of the carbon templates, morphology-controlled perovskites using activated carbons and a non-templated catalyst were prepared to determine how carbon templates influence the chemical structure of the perovskite. The carbon templates produced a crystalline structure with the well incorporation of Ru under mild calcination conditions. The morphology of the hollow fibers provided a higher specific surface area than that of the porous grain catalyst with a similar average particle size (∼80 nm). It was found that the hollow fibers showed a unique pore structure with large macropores from 1 to 100 μm, which might offer a higher surface area and enhanced mass transfer of the reactants. This provided a higher activation energy for H2 production than the porous grain and non-templated catalysts during the autothermal reforming of heavy hydrocarbons. As a result, the fibrous feature and well-defined chemical structure were crucial factors when cracking the hydrocarbon chain. The hollow fiber catalyst showed high reforming efficiency for H2 production (>65 mol%) from heavy-hydrocarbon fuels during long-term experiments, featuring substantial durability with low carbon deposition and no structural changes.